2016
DOI: 10.3733/ucanr.8560
|View full text |Cite
|
Sign up to set email alerts
|

Poisonous Plants

Abstract: Extension, Kern CountyPoisonous Plants T his publication describes typical adverse symptoms and health effects that selected common poisonous plants and plant parts can cause in people. It also includes a table of poisonous plants commonly found around the home and garden and explains how to make a plant identification file. Plants associated with poisonings and other health problems that have been frequently reported throughout the state to the California Poison Control System are listed. Plant species that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…All over the world, some plants because of their toxic potential are recognized for being a threat to animals due to the compounds produced by these plants such as alkaloids, terpenes, cardiac and cyanogenic glycosides, proanthocyanidins, nitrogen‐containing compounds, and others (Alsop & Karlik, 2016; Dubey, Dwivedy, Chaundhari, & Das, 2018). Several countries or regions provide guides, veterinary manuals, or other documents about common poisonous or toxic plants that can affect animals, in an attempt to use approaches to manage and reduce animal losses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All over the world, some plants because of their toxic potential are recognized for being a threat to animals due to the compounds produced by these plants such as alkaloids, terpenes, cardiac and cyanogenic glycosides, proanthocyanidins, nitrogen‐containing compounds, and others (Alsop & Karlik, 2016; Dubey, Dwivedy, Chaundhari, & Das, 2018). Several countries or regions provide guides, veterinary manuals, or other documents about common poisonous or toxic plants that can affect animals, in an attempt to use approaches to manage and reduce animal losses.…”
Section: Resultsmentioning
confidence: 99%
“…The dose is the determining factor for toxicity; hence, the most dangerous plants are lethal to animals if they consume large amounts in a short time. Furthermore, the toxic potential is related to other variables as the potency of the toxicant, the concentration of the toxic compound in the plant or part of the plant, the route of exposure, the amount absorbed, the sensitivity of the animal species to the toxicant and its physiological status, seasonal and regional variations in the plant, the mode of action, and the organ or system affected (Alsop & Karlik, 2016; Poutaraud et al., 2017). To prevent accidental poisoning during grazing, rangelands may be in good condition to avoid that animals eat other plants in the absence of the regular ones (Welch et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that calcium-based sorbents gradually lose their CO 2 capture capacity as they are subjected to successive carbonation/calcination cycles due to solids sintering. ,,, The decrease in solids activity is compensated for by a makeup flow of fresh sorbent, which is an important design parameter of the system. At the highest level of integration between the CaL system and the cement plant, the raw meal itself, which is typically composed of around 80 wt % of CaCO 3 , acts as the calcium-based sorbent . However, there is very little experimental evidence to confirm the effectiveness of cement raw meal as a CO 2 capture sorbent. It is well-known that belite (Ca 2 SiO 4 ) can be produced under typical cement precalciner conditions either via the direct reaction of CaCO 3 with SiO 2 (eq ) or via the reaction of CaO with SiO 2 (eq ).…”
Section: Introductionmentioning
confidence: 99%
“…10,23−28 The highest level of integration can be achieved if the source of CaO for the CaL systems is the cement raw meal itself, instead of limestone, 24,25,28 taking advantage of the fact that a typical raw meal contains approximately 80 wt % of CaCO 3. 29 In this configuration, the precalciner of the cement plant is switched to oxy-fuel combustion mode and hence it is used as the calciner of a CaL system. 24,25,28 In the carbonator, only the CO 2 from the additional fuel combustion and residual calcination of the sorbent in the rotary kiln is captured.…”
Section: Introductionmentioning
confidence: 99%
“…The synergies between the CaL technology and the cement sector have been recognized almost from the beginning of the CaL development. There are different possibilities to apply this technology to the cement sector for which the integration level with the cement plant will be different. , The highest level of integration can be achieved if the source of CaO for the CaL systems is the cement raw meal itself, instead of limestone, ,, taking advantage of the fact that a typical raw meal contains approximately 80 wt % of CaCO 3. In this configuration, the precalciner of the cement plant is switched to oxy-fuel combustion mode and hence it is used as the calciner of a CaL system. ,, In the carbonator, only the CO 2 from the additional fuel combustion and residual calcination of the sorbent in the rotary kiln is captured . Although the inert materials present in the raw meal will affect the energy balance in the CaL, by increasing the heat requirements in the calciner, it is well understood that the large makeup will compensate the energy penalties by increasing the average activity of the sorbent. ,, …”
Section: Introductionmentioning
confidence: 99%